Genetic structure of West Greenland populations of lumpfish Cyclopterus lumpus. Issue 6 (17th October 2016) - Garcia‐Mayoral, E.; Olsen, M.; Hedeholm, R.; Post, S.; Nielsen, E. E.; Bekkevold, D.
Abstract : In this study, 11 microsatellite markers were used to determine the structure of West Greenlandic lumpfish Cyclopterus lumpus populations across six spawning locations spanning >1500 km and compared with neighbouring populations in Canada and Iceland. To evaluate whether data allow for identification of origin of C. lumpus in Greenlandic waters, genetic assignment analysis was performed for 86 C. lumpus sampled on a feeding migration. Significant structuring with isolation by distance was observed in the West Greenland samples and two major subpopulations, north and south, were suggested. Based on F ST values, closer relationships were observed between Greenland and Canada, than Greenland and Iceland. Surprisingly, the North Greenland population showed more similarities with Canadian samples, than did the geographically closer south‐west Greenland population. Origin could be assigned for a high proportion of non‐spawning fish and demonstrated a marked east–west spatial separation of fish of Greenlandic and Icelandic genotypes.